VEGF-induced endothelial cell migration requires urokinase receptor (uPAR)-dependent integrin redistribution - Alexander, Revu Ann (Cardiovasc Res, 2012)
AIMS: Vascular endothelial growth factor (VEGF)-initiated angiogenesis requires coordinated proteolytic degradation of extracellular matrix provided by the urokinase plasminogen activator/urokinase receptor (uPA/uPAR) system and regulation of cell migration provided by integrin–matrix interaction. In this study, we investigated the mechanisms underlying the uPAR-dependent modulation of VEGF-induced endothelial migration. METHODS AND RESULTS: We used flow cytometry to quantify integrins at the cell surface. Stimulation of human and murine endothelial cells with VEGF resulted in internalization of α5β1-integrins. Micropatterning and immunocytochemistry revealed co-clustering of uPAR and α5β1-integrins and retrieval via clathrin-coated vesicles. It was also contingent on receptors of the low-density lipoprotein receptor (LDL-R) family. VEGF-induced integrin redistribution was inhibited by elimination of uPAR from the endothelial cell surface or by inhibitory peptides that block the uPAR–integrin interaction. Under these conditions, the migratory response of endothelial cells upon VEGF stimulation was impaired both in vitro and in vivo. CONCLUSIONS: The observations indicate that uPAR is an essential component of the network through which VEGF controls endothelial cell migration. uPAR is a bottleneck through which the VEGF-induced signal must be funnelled for both focused proteolytic activity at the leading edge and for redistribution of integrins.